2018
DOI: 10.4103/0366-6999.229896
|View full text |Cite
|
Sign up to set email alerts
|

Limited Role of Promoter Methylation of MGMT and C13ORF18 in Triage of Low-Grade Squamous Intraepithelial Lesion

Abstract: Background:Promoter methylation of MGMT and C13ORF18 has been confirmed as a potential biomarker for early diagnosis of cervical cancer. The aim of this study was to evaluate the performance of MGMT and C13ORF18 promoter methylation for triage of cytology screening samples and explore the potential mechanism.Methods:Methylation-sensitive high-resolution melting was used to detect promoter methylation of MGMT and C13ORF18 in 124 cervical samples. High-risk human papillomavirus (HR-HPV) was detected by the Digen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…The triage capacity of DNA methylation in our study was in accordance with previous reports [28,35]. However, studies on various DNA methylation triage methods in the Chinese population have reached conflicting conclusions [37][38][39]. These discrepancies reflect bias associated with the selected study populations and candidate genes.…”
Section: Discussionsupporting
confidence: 91%
“…The triage capacity of DNA methylation in our study was in accordance with previous reports [28,35]. However, studies on various DNA methylation triage methods in the Chinese population have reached conflicting conclusions [37][38][39]. These discrepancies reflect bias associated with the selected study populations and candidate genes.…”
Section: Discussionsupporting
confidence: 91%
“…In China, plenty of studies have been conducted in the recent years to explore the usage of methylation of human genes (including FAM19A4/EPB41L3/JAM3/MGMT/C13ORF18/ANKRD18CP/ C13ORF18/EPB41L3/JAM3/SOX1/ZSCAN1) in the field of cervical cancer screening, but all those studies were conducted in the clinic settings with relatively small sample size (ranging from 124 to 588). [19][20][21][22][23] Only one study indicated methylation test played a limited role, 21 the other studies showed that the methylation alone or in combination with HPV16/18 could be used as the primary screening testing or triage method for hrHPV positive women. The study with the largest sample size conducted by Gu et al supported that the S5 methylation panel at 2.85 cutoff was superior to HPV16/18 genotyping and cytology for histology HSIL+ (highgrade squamous intraepithelial lesion or worse) detection.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Promoter methylation of RUBCNL was identified as a potential biomarker for early diagnosis of cervical cancer. 44 BIRC3, baculoviral IAP repeat-containing protein 3, as an apoptosis inhibitor, was overexpressed in multiple cancers and led to development of malignant tumors. [45][46][47][48][49][50] Upregulation of BIRC3 promoted prostate cancer development and inhibited NK cell activities.…”
Section: Discussionmentioning
confidence: 99%
“…FADS3, as a fatty acid desaturase, was located along with FADS1 and FADS2, 41 which were reported to be associated with the occurrence and development of NSCLC and colon cancer 42,43 . Promoter methylation of RUBCNL was identified as a potential biomarker for early diagnosis of cervical cancer 44 . BIRC3, baculoviral IAP repeat‐containing protein 3, as an apoptosis inhibitor, was overexpressed in multiple cancers and led to development of malignant tumors 45–50 .…”
Section: Discussionmentioning
confidence: 99%